Fruit and vegetable intake and body adiposity among populations in Eastern Canada: the Atlantic Partnership for Tomorrow's Health Study. Issue 4 (10th April 2018) - Yu, Zhijie Michael; DeClercq, Vanessa; Cui, Yunsong; Forbes, Cynthia; Grandy, Scott; Keats, Melanie; Parker, Louise; Sweeney, Ellen; Dummer, Trevor J B
Abstract : Objectives: The prevalence of obesity among populations in the Atlantic provinces is the highest in Canada. Some studies suggest that adequate fruit and vegetable consumption may help body weight management. We assessed the associations between fruit and vegetable intake with body adiposity among individuals who participated in the baseline survey of the Atlantic Partnership for Tomorrow's Health (Atlantic PATH) cohort study. Methods: We carried out a cross-sectional analysis among 26 340 individuals (7979 men and 18 361 women) aged 35–69 years who were recruited in the baseline survey of the Atlantic PATH study. Data on fruit and vegetable intake, sociodemographic and behavioural factors, chronic disease, anthropometric measurements and body composition were included in the analysis. Results: In the multivariable regression analyses, 1 SD increment of total fruit and vegetable intake was inversely associated with body mass index (−0.12 kg/m 2 ; 95% CI −0.19 to –0.05), waist circumference (−0.40 cm; 95% CI −0.58 to –0.23), percentage fat mass (−0.30%; 95% CI −0.44 to –0.17) and fat mass index (−0.14 kg/m 2 ; 95% CI −0.19 to –0.08). Fruit intake, but not vegetable intake, was consistently inversely associated with anthropometric indices, fat mass, obesity and abdominal obesity. Conclusions: Fruit and vegetable consumption was inversely associated with body adiposity among the participant population in Atlantic Canada. This association was primarily attributable to fruit intake. Longitudinal studies and randomised trials are warranted to confirm these observations and investigate the underlying mechanisms.